Assessing the greenhouse gas mitigation potential of urban precincts with hybrid life cycle assessment. (10th January 2021) - Yu, Man; Wiedmann, Thomas; Langdon, Sarah
Abstract: As the critical link between individual building and city, precinct represents an important scale for urban planning, at which low-carbon strategies for urban built environment can be tested and measured. However, previous studies often failed to assess the life cycle greenhouse gas (GHG) emissions from the urban precincts comprehensively and reliably due to methodological and data-related limitations. This study is conceived to bridge this gap by applying a case-specific hybrid life cycle assessment (LCA) to a typical residential precinct including buildings, open spaces, network, on-site energy units and occupant-related mobility. Meanwhile, the corresponding conventional process-based LCA is conducted alongside to quantify the impact of applying different LCA approaches. For the whole precinct, the life cycle GHG emissions from hybrid LCA is 16% higher than its corresponding process-based LCA result, reaching 16.6 t CO2 e/inhabitant/year. Embodied emissions, operational emissions and occupant-related transport emissions take up 28%, 32% and 40% of the life cycle GHG emissions, respectively, and the biggest difference between these two LCA approaches is seen in embodied emissions (22%), followed by transport emissions (17%) and operational emissions (11%). Assuming no technology innovation and substantial changes in economic structure, precinct design and lifestyle are involved, twelve GHG emissions mitigation measures are quantified. While process-based LCA suggests a mitigation potential of 35%, hybrid LCA results in a reduction of 31%. The most effective measures are related to reducing transport emissions and operational emissions, but for the embodied emissions, instead of reducing them, the combination of all measures brings about a slight increase both absolutely and relatively. From base case to mitigated case, the differences between two LCA approaches are enlarged and the biggest difference is always seen in embodied emission. This implies the process-based LCA would further underestimate the life cycle GHG emissions in mitigated case, therefore, the use of hybrid LCA is more favourable for the purpose of providing a comprehensive and reliable assessment. Highlights: The life cycle GHG emissions of the precinct is 16.6 t CO2 e/inhabitant/year. Before taking mitigation, occupant-related transport is the largest contributor. Twelve mitigation measures can reduce the life cycle GHG emissions by 31%. After taking mitigation, embodied emissions take up 44% of the overall emissions. The difference between process-based and hybrid LCA is enlarged from 16% to 23%.